THE FORMATION OF NEW DIRECTIONS IN THE FIELD OF FINE ARTS IN UZBEKISTAN IN THE SECOND HALF OF THE XX CENTURY - Asrorbek Hamroev Bakhtiarivic (European Science Publishing, 2024)
In this article cites the fact that the first achievements and searches of Uzbek art in the second half of the 20th century appeared in the genre of portraits and landscapes, the respect and attention of artists to life, people, personal experiences were expressed in works of this genre. As well as the fact that monumental art has moved to the stage of development, Ch.In the work of Ahmarov, the first example of this was created, the achievements of architectural art A.Babakhanov, M.The manifestation in Bulatov and other mature works is shown on the basis of sources that the 50s were the period of the initial laying of the siege stone for the transition of modern Uzbek art to a new era.
Keywords: Monumental art